Medico-legal Study of Shockwave Damage by High Velocity Missiles in Firearm Injuries - Selman, Yasser S.; Hashim, Nabeel G.; Al-Naaimi, Ahmed S.; Saeed, Ahmed S. (Journal of the Faculty of Medicine Baghdad, 2012)
Background: Many variables determine the destructive capacity of a weapon; missile velocity is an important consideration. Wounding capability of a missile depends on the amount of kinetic energy dissipated in the tissues. A penetrating high velocity missile (usually bullets) transfers a destructive energy called shock wave to the surrounding tissues.Objective: To detect and estimate tissues damage away from the main track of high velocity missiles in firearm rifled weapons injuries.Methods: This cross-sectional study is performed in medico-legal institute in Baghdad for (8) month’s duration from (1-1-2010) to (1-9-2010). Full proper autopsy including external and internal examination of the body for all cases was performed, and complete medico-legal history was obtained to determine the type of the weapon used so as to include only the cases of high velocity missile injures.Results: The study included (30) cases; (21) men and (9) women with their ages ranged between (15 –70) years. The total body injures in all cases were (69) in the main track and (43) away from the main track of the missiles. Head and neck region was affected more than other body regions by primary injury, while the chest region was the most affected by distant injuries due to shock wave.Conclusion: The shock wave damage had happened in all cases of high velocity missile firearm injures in this study. Most of them were in the chest; the lower limbs were the least frequently affected. This should be put in consideration of forensic pathologist.